Bottlenecks in Anemia Prevention and Control in the West Bank and Gaza Strip : Assessment Report - World Bank (Washington, DC: World Bank, 2022)
According to the information available and the thresholds established by World Health Organization (WHO)E, anemia is a public health problem among the most vulnerable groups in the Palestinian Territory, namely pregnant and postpartum women, children aged between 6-59 months, and adolescents aged 15-18 years. The burden of anemia has remained static during the last decade, suggesting that the anemia prevention and control (APC) interventions in place have not produced their expected outcomes. This assessment, therefore, identifies and analyzes bottlenecks in the ongoing interventions to provide insights to strengthen APC in the West Bank and Gaza Strip (WB & GS). The three main APC activities identified in the Palestinian Territory were the universal fortification of wheat flour with micronutrients, iron supplementation to pregnant and postnatal women and children aged between 6-23 months, and the promotion of an increased dietary intake of micronutrients.